2019
DOI: 10.1149/09101.2225ecst
|View full text |Cite
|
Sign up to set email alerts
|

Improved Robustness and Low Area Specific Resistance with Novel Contact Layers for the Solid Oxide Cell Air Electrode

Abstract: Talic, B.; Ritucci, I.; Kiebach, R.; Hendriksen, P. V.; Frandsen, Henrik LundStacking of solid oxide cells (SOC) requires that a robust and durable electrical contact between the cell and the interconnect is established. In this work we present a new contact layer solution for the SOC air side, based on the concept of reactive oxidative bonding. The contact layer consists of metallic Mn-Co and Mn-Cu particles that during initiation/operation are oxidized in-situ to form well-conductive spinel oxides. The long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this approach, metallic particles (Co-Mn, Cu-Mn) are deposited, which through the assembly of the stack oxidize to well conducting spinels. The oxidative reaction through the forming of the spinels assists the sintering process and increases the adherence by a factor 5 or 10 for the CoMn and CuMn contact layers, respectively (1,7). This research is undertaken in the EU project LOWCOST-IC and the plan is to test these contact layers together with novel coating and steel compositions in stacks from the companies SOLIDpower and Sunfire.…”
Section: Recent Achievementsmentioning
confidence: 99%
“…In this approach, metallic particles (Co-Mn, Cu-Mn) are deposited, which through the assembly of the stack oxidize to well conducting spinels. The oxidative reaction through the forming of the spinels assists the sintering process and increases the adherence by a factor 5 or 10 for the CoMn and CuMn contact layers, respectively (1,7). This research is undertaken in the EU project LOWCOST-IC and the plan is to test these contact layers together with novel coating and steel compositions in stacks from the companies SOLIDpower and Sunfire.…”
Section: Recent Achievementsmentioning
confidence: 99%
“…It suggests that the cyclic test had a minimal effect on the ASR performance for the test cell with this alloy contact precursor, most likely due to the excellent CTE match between the contact layer and other cell components. The increased ASR during may be triggered by partial oxide scale spallation which could lead to a decrease in the effective contact area between the substrate and contact area [35,36]. According to the ASR performance, it can be concluded that the CuMnNiFeCo alloy was suitable as the candidate material for SOFC cathodecontact application.…”
Section: Electrical Performance Of the Test Cellmentioning
confidence: 99%
“…With time, the outward diffusion of Cr may deteriorate the electrical conductivity and fracture energy of the interface. Based on ASR measurements with a similar contact layer material, made by screen-printing a paste with Cu and Mn metal particles, the outward diffusion of Cr is not expected to have a negative influence on the electrical properties [51]. Nevertheless, we are currently investigating the effect of aging on the ASR and fracture energy of the CuMn foam/MCO-IC interface and will report the results elsewhere.…”
Section: Reaction Assisted Bondingmentioning
confidence: 99%
“…Based on ASR measurements with a similar contact layer material, made by screen-printing a paste with Cu and Mn metal particles, the outward diffusion of Cr is not expected to have a negative influence on the electrical properties. 51 Nevertheless, we are currently investigating the effect of aging on the ASR and fracture energy of the CuMn foam/MCO-IC interface and will report the results elsewhere. In summary, the high fracture energies achieved with the CuMn foam can be explained by (1) the high deformability of the foam in its metallic state, enabling it to accommodate manufacturing tolerances and achieve a larger contact area to the adjoining surface; (2) the in situ oxidation and associated volume expansion, during which the foam can expand into the porous structure of the adjoining surface, thereby creating a mechanical interlocking; and finally, (3) the reactivity between the oxidized foam and the adjoining surface, forming chemical bonds.…”
Section: Lsm Interfacesmentioning
confidence: 99%